Plasma Simvastatin Variations with CYP3A4*22 and CYP3A5*3 (Precision Medicine Communications, 2022)
CYP3A4, the major microsomal enzyme involved in drug metabolism, catalyzes the biotransformation of Simvastatin. An integrated genotypic categorization of CYP3A4/5 comprising CYP3A4*22 (decrease of function) and CYP3A5*3 (loss of function) was documented. Associations of the aforementioned alleles and the simvastatin acid (SVA), as well as simvastatin lactone (SVL) plasma levels, were studied by Joseph and colleagues. This work is the first to investigate the in vivo simvastatin levels and CYP3A4*22 polymorphism. A cohort of 275 African Americans and 555 Caucasians, making up 830 patients in a Cholesterol and Pharmacogenomics clinical trial, were recruited. The concentration of simvastatin was determined in 12-h post-dose samples. As a combined genotypic category and individually, the CYP3A4*22 and CYP3A4*3 alleles were tested to see any associations. In Caucasians, there were 513 non-carriers of CUP4A4*22 and 42 carriers. It was observed that 14% higher SVA (P=0.04) and 20% higher SV (P=0.06) levels were seen in Caucasian carriers compared to non-carriers. However, CYP3A5*3 allele status bore no significant association with SV or SVA. The African American population had eight carriers and 267 non-carriers of CYP3A4*22 alleles. No significant difference was seen in African Americans' SVA levels and CYP3A4*22 alleles. However, carriers had 170% higher SV (P<0.01) than noncarriers. African-American CYP3A5 nonexpressers (n=28) had 33% higher SV (P=0.02) than CYP3A5 expression (n=247), but no significant difference was detected for SVA. Contrasting results for both SV and SVA where the SV displayed a decrease in CYP3A4/5 groups (poor, intermediate, and extensive metabolizers). In both self-reported Caucasians and African Americans, associations were seen between CYP3A4 and CYP3A5 with plasma concentrations of simvastatin.Pharmacogenet Genomics (2014) DOI; 10.1097/FPC.0000000000000079.